2016
DOI: 10.1108/bfj-12-2015-0479
|View full text |Cite
|
Sign up to set email alerts
|

How convenient!? Adolescents’ vistas on food competences in a convenience context

Abstract: Purpose Adolescents are at a stage in their life course in which they increasingly become choosers, buyers and preparers of food. Hence, they develop and employ required competences. Current food-related competences of adolescents are shaped in an environment with an abundance of convenience foods. Simultaneously food education has been limited in many western countries. The purpose of this paper is to scrutinize how young practitioners engage with the notion of convenience in a context with a strong presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Prior studies investigating attitudes towards cutlery use is sparse, but this omission of cutlery is supported by an adolescent focus group study which revealed individuals avoided foods requiring cutlery because using it would be an 'embarrassment' (Stead et al, 2011). Moreover, whilst adolescents do not appreciate food preparation skills, convenience is highly regarded by adolescent consumers, yet they often perceive convenience products to have negative health implications (Wahlen, van der Horst, & Pothoff, 2016). Therefore, it is important that NPD targeting this market ensure that snacking products are convenient yet also suitably healthful.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies investigating attitudes towards cutlery use is sparse, but this omission of cutlery is supported by an adolescent focus group study which revealed individuals avoided foods requiring cutlery because using it would be an 'embarrassment' (Stead et al, 2011). Moreover, whilst adolescents do not appreciate food preparation skills, convenience is highly regarded by adolescent consumers, yet they often perceive convenience products to have negative health implications (Wahlen, van der Horst, & Pothoff, 2016). Therefore, it is important that NPD targeting this market ensure that snacking products are convenient yet also suitably healthful.…”
Section: Discussionmentioning
confidence: 99%